Analisis Nilai Karakter Ormas NU Dalam Perspektif Pendidikan Kewarganegaraan - Rizqi, Ascosenda Ika; Sapriya, Sapriya; Abdulkarim, Aim; Sundawa, Dadang (Jurnal Civic Hukum, 2024)
The aim of this research is to examine the religious form of religious life in the form of Aswaja which has taken root among members of the Nahdlatul Ulama mass organization as a character value of the community organization. This study uses ethnographic research where ethnography can analyze a social group, behavior and language. The research location was carried out in the City of Pasuruan, East Java, which is one of the largest Nadhlatul Ulama bases that is embraced by the people of the Pasuruan region in general. The results of this study are in accordance with the concept of Citizenship Education including the values of Tawassuth, Fikrah Ishlahiyyah, I'tidal, Tawazun, Tasamuih, Fikrah Tasamuhiyah, Amar Ma'ruf Nahi Munkar, Fikrah Tathawwuriyah, Fikrah Tawassuthiyah and Fikrah Manhajiyah.